2018
DOI: 10.2116/analsci.18p497
|View full text |Cite
|
Sign up to set email alerts
|

Microliter Operation for Determination of Nitrate-Nitrogen via Simple Zinc Reduction and Color Formation in a Well Plate with a Smartphone

Abstract: We propose a simple greener colorimetric method for the determination of nitrate-nitrogen by operating on a 96-well microplate and using a smartphone camera as a simple detector. A slurry containing 0.3 mg zinc was used for reduction of nitrate to nitrite, the reduction solution was transferred to a 96-well microplate to react with Griess reagent to form a pink azo dye product. The color product image was captured and processed by a smartphone camera and ImageJ software, respectively. The limit of detection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Accordingly, 200 μL of the sample and 50 μL of reagent solution were fixed for all assays. In detail, the analytical procedure consisted of the following steps (as shown in Figure 7 ): (a) a microplate was placed on a pad for the guide taking the solution to a micro-well; (b) the standard solution was taken to the well; (c) the sample was placed in the well; (d) the reagent was prepared by dissolving it in ID water; (e) the reagent was mixed with the sample solution; (f) the mixture was incubated before measurement of color; (g) this microplate was placed in a lightbox; (h) the colors were detected by a smart device camera (Apple iPhone8, China) on a light-control box [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, 200 μL of the sample and 50 μL of reagent solution were fixed for all assays. In detail, the analytical procedure consisted of the following steps (as shown in Figure 7 ): (a) a microplate was placed on a pad for the guide taking the solution to a micro-well; (b) the standard solution was taken to the well; (c) the sample was placed in the well; (d) the reagent was prepared by dissolving it in ID water; (e) the reagent was mixed with the sample solution; (f) the mixture was incubated before measurement of color; (g) this microplate was placed in a lightbox; (h) the colors were detected by a smart device camera (Apple iPhone8, China) on a light-control box [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly used reducing agents are cadmium, copperized cadmium, zinc, nitrate reductase, hydrazine sulfate, titanium (III) chloride, or vanadium (III) [28,31]. Cadmium reduction is the leading method used for nitrate detection; however, more researchers are using zinc since it is a less toxic reductant and not as harmful to humans or the environment as cadmium [43,44]. Moreover, it is worth mentioning that Jayawardane et al [33] obtained similar results for nitrate detection when using cadmium or zinc in a paper-based microfluidic device.…”
Section: The Greiss Assaymentioning
confidence: 99%
“…Since the advent of commercial digital cameras in the 1990s, studies on analysis using digital images 1,2 have been reported. Recently, not a few studies using general photographing equipment, especially smartphones, [3][4][5] have been published for quantitation.…”
Section: Introductionmentioning
confidence: 99%